Assessing Fish Immunotoxicity by Means of In Vitro Assays: Are We There Yet? - Segner, Helmut; Rehberger, Kristina; Bailey, Christyn; Bo, Jun (Frontiers in Immunology, 2022)
There is growing awareness that a range of environmental chemicals target the immune system of fish and may compromise the resistance towards infectious pathogens. Existing concepts to assess chemical hazards to fish, however, do not consider immunotoxicity. Over recent years, the application of in vitro assays for ecotoxicological hazard assessment has gained momentum, what leads to the question whether in vitro assays using piscine immune cells might be suitable to evaluate immunotoxic potentials of environmental chemicals to fish. In vitro systems using primary immune cells or immune cells lines have been established from a wide array of fish species and basically from all immune tissues, and in principal these assays should be able to detect chemical impacts on diverse immune functions. In fact, in vitro assays were found to be a valuable tool in investigating the mechanisms and modes of action through which environmental agents interfere with immune cell functions. However, at the current state of knowledge the usefulness of these assays for immunotoxicity screening in the context of chemical hazard assessment appears questionable. This is mainly due to a lack of assay standardization, and an insufficient knowledge of assay performance with respect to false positive or false negative signals for the different toxicant groups and different immune functions. Also the predictivity of the in vitro immunotoxicity assays for the in vivo immunotoxic response of fishes is uncertain. In conclusion, the currently available database is too limited to support the routine application of piscine in vitro assays as screening tool for assessing immunotoxic potentials of environmental chemicals to fish.